Information acquisition during a Dutch auction - Paavo Miettinen (Bank of Finland, 2012)
In this paper we consider equilibrium behavior in a Dutch (descending price) auction when the bidders that are uninformed of their valuations with probability q and can acquire information about their valuation with a positive cost during the auction. We assume that the information acquisition activity is covert. We characterize the equilibrium behavior in the setting where bidders are ex ante symmetric and have independent private values. We show that when the number of bidders is large the Dutch auction produces more revenue than the first price auction.
URN:NBN:fi:bof-20140807383
Keywords: 330